(3GdPNjQIs - (3Ydj Hf jhfS GdYGedj GdfHGWjs
(3ChdgG (B:s
(3hHYO aGYde QGTOkG eG bdJ eYhdkG Ydi GdPi fXeJ deG bVi GdfHi bGdJ WGFaI fVH Ydi YdeG s
(3BNQgG (B:s
(3SejJgG PNjQI GdEjeGf gOjI efi Edi GdENhGf JeJ HMeO Gddg hMSf Jhajbg hUdi Gddg Ydi eMeO hBdg s
(3bUjOIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds